Blocking Protein Phosphatase 1 [PP1] Prevents Loss of Tether Elasticity in Anaphase Crane-Fly Spermatocytes - Forer, Arthur; Adil, Aisha; Berns, Michael W. (Frontiers in Molecular Biosciences, 2021)
In normal anaphase cells, telomeres of each separating chromosome pair are connected to each other by tethers. Tethers are elastic at the start of anaphase: arm fragments cut from anaphase chromosomes in early anaphase move across the equator to the oppositely-moving chromosome, telomere moving toward telomere. Tethers become inelastic later in anaphase as the tethers become longer: arm fragments no longer move to their partners. When early anaphase cells are treated with Calyculin A (CalA), an inhibitor of protein phosphatases 1 (PP1) and 2A (PP2A), at the end of anaphase chromosomes move backward from the poles, with telomeres moving toward partner telomeres. Experiments described herein show that in cells treated with CalA, backwards movements are stopped in a variety of ways, by cutting the tethers of backwards moving chromosomes, by severing arms of backwards moving chromosomes, by severing arms before the chromosomes reach the poles, and by cutting the telomere toward which a chromosome is moving backwards. Measurements of arm-fragment velocities show that CalA prevents tethers from becoming inelastic as they lengthen. Since treatment with CalA causes tethers to remain elastic throughout anaphase and since inhibitors of PP2A do not cause the backwards movements, PP1 activity during anaphase causes the tethers to become inelastic.